FORENSIC PATHOLOGY AND ITS CONTRIBUTION TO CRIMINAL JUSTICE (International journal of artificial intelligence, 2025)
Forensic pathology is a cornerstone of forensic medicine, providing courts and investigators with scientific evaluations of death, injury, and disease in legal contexts. By conducting autopsies, analyzing injury patterns, and interpreting pathological findings, forensic pathologists determine the cause and manner of death. This article explores the history, scope, and methodologies of forensic pathology, emphasizing its role in homicide investigations, accident reconstruction, and the protection of human rights. The paper also discusses current challenges, such as workload, ethical considerations, and the impact of new technologies, while highlighting future directions in education, research, and interdisciplinary collaboration.